Respostas
respondido por:
0
b) cancelar a base 5 pois é igual
x²+4=5x
x²-5x+4=0
∆=(-5)²-4.1.4
∆=25-16
∆=9
x=5±√9/2.1
x=5±3/2
x1= 5+3/2=8/2=4
x2=5-3/2=2/2=1
S={4,1}
c) (9²)^2x= 9^x-15
9^4x=9^x-15
4x=x-15
4x-x=-15
3x=-15
x=-15/3
x=-5
S={-5}
x²+4=5x
x²-5x+4=0
∆=(-5)²-4.1.4
∆=25-16
∆=9
x=5±√9/2.1
x=5±3/2
x1= 5+3/2=8/2=4
x2=5-3/2=2/2=1
S={4,1}
c) (9²)^2x= 9^x-15
9^4x=9^x-15
4x=x-15
4x-x=-15
3x=-15
x=-15/3
x=-5
S={-5}
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás